Discovery of key regulators of dark gland development and hypericin biosynthesis in St. John's Wort (Hypericum perforatum) - Rizzo, Paride; Altschmied, Lothar; Stark, Pauline; Rutten, Twan; Gündel, André; Scharfenberg, Sarah; Franke, Katrin; Bäumlein, Helmut; Wessjohann, Ludger; Koch, Marcus; Borisjuk, Ljudmilla; Sharbel, Timothy F. (Plant biotechnology journal, 2019)
Hypericin is a molecule of high pharmaceutical importance that is synthesized and stored in dark glands (DGs) of St. John's Wort (Hypericum perforatum). Understanding which genes are involved in dark gland development and hypericin biosynthesis is important for the development of new Hypericum extracts that are highly demanded for medical applications. We identified two transcription factors whose expression is strictly synchronized with the differentiation of DGs. We correlated the content of hypericin, pseudohypericin, endocrocin, skyrin glycosides and several flavonoids with gene expression and DG development to obtain a revised model for hypericin biosynthesis. Here, we report for the first time genotypes which are polymorphic for the presence/total absence (G+/G−) of DGs in their placental tissues (PTs). DG development was characterized in PTs using several microscopy techniques. Fourier transform infrared microscopy was established as a novel method to precisely locate polyaromatic compounds, such as hypericin, in plant tissues. In addition, we obtained transcriptome and metabolome profiles of unprecedented resolution in Hypericum. This study addresses for the first time the development of dark glands and identifies genes that constitute strong building blocks for the further elucidation of hypericin synthesis, its manipulation in plants, its engineering in microbial systems and its applications in medical research.
Gesehen am 27.11.2019